Strategi Humas melalui Media Online dalam Membangun Citra MI Miftahul Akhlaqiyah Semarang - Nani Nafisaturohmah; Abdul Wahid; Baqiyatush Sholihah (Jawda: Journal of Islamic Education Management, 2021)
MI Miftahul Akhlaqiyah Semarang is a private school located in the beringin region, Ngaliyan. In this environment there are many elementary schools. So that the school needs to introduce the school program to the community. The website is one of the media choices chosen by MI Miftahul Akhlaqiyah in building the image of the school. The focus of the problems taken in this study is: How is the Public Relations Strategy through Online Media in Building the Image of MI Miftahul Akhlaqiyah Semarang? This research uses a type of field research with a descriptive qualitative approach. Collecting data using several methods, namely: observation, interviews and documentation. The results showed that, (1) to facilitate user access, namely the existence of adequate facilities, ease of finding websites, mobile friendly, simple website operation, the presence of the most current and most popular news notifications, and access speed. However, the MI Miftahul Akhlaqiyah website does not have a Navigation feature. (2) The MI Miftahul Akhaqiyah website has a large number of visitors and has a global scope. (3) the MI Miftahul Akhlaqiyah website cannot communicate between visitors, but can only be done between visitors and managers.